Utility of bedside leucocyte esterase testing to rule out septic arthritis. Issue 9 (10th March 2021) - Knapper, Thomas; Murphy, Richard J; Rocos, Brett; Fagg, James; Murray, Nick; Whitehouse, Michael Richard
Abstract : Introduction: Suspected septic arthritis is a common presentation to EDs. The underlying diagnosis is often non-infective pathology. Differentiating between aetiologies is difficult. A bedside test with high negative predictive value (NPV) may allow safe discharge of patients, reduce the time in the ED, hospital admission and associated costs. This study aims to evaluate the NPV of bedside leucocyte esterase (LE) in the assessment of these patients. Methods: A prospective multicentre observational study of ED adult patients referred to orthopaedics with suspected native joint septic arthritis between October 2015 and April 2016. At three hospital sites in the Bristol region, the results of the LE test exposed to aspirated synovial fluid were recorded along with Gram stain, culture, haematinics and length of stay. A positive LE test was considered 2+ or 3+ leucocytes based on the test strip colour. Data were analysed to establish sensitivity, specificity, NPV and positive predictive value (PPV) against the gold standard 48-hour culture. We determined the potential number of inpatient bed-days that might be avoided using this bedside test. Results: Eighty patients underwent joint aspiration. Five cases had positive 48-hour culture. All (5/5) infected cases showed ≥2+ LE, sensitivity of 100% (95% CI 47.8% to 100%) while the Gram stain was positive in only one case (sensitivity 20%, 95% CI 0.51% to 71.6%). Twenty-three LE were read negative or 1+, all with negative 48-hour culture results, resulting in an NPV of 100% (95% CI 82.1% to 1.00%) for a negative LE test. Specificity of a positive LE test was 30.7% (95% CI 20.5% to 42.45%) with PPV of 8.77% (95% CI 7.64% to 10.1%). It was calculated that 57 orthopaedic bed-days could have potentially been saved by immediately discharging those with a negative LE test. Conclusions: LE point-of-care testing for suspected septic arthritis of native joints has a high NPV. Implementation of LE may facilitate more rapid discharge of patients with negative results. This test has the potential to reduce diagnostic uncertainty and costs to the healthcare system.